THE EFFECT OF CURRICULUM 2013 ON ECONOMICS LEARNING ACHIEVEMENT: MOTIVATION AS A MEDIATING VARIABLE - Ananda Setiawan; Sri Umi Mintarti Widjaja; Djoko Dwi Kusumajanto; Hari Wahyono (LPMPP Universitas Negeri Yogyakarta, 2020)
The National Standard of Education (NSE) in Indonesia is a legitimate instrument to reach the best achievement. Yet, there are still the other positive factors, especially on economics subjects. This research aimed to find out the direct effect of the national standard of education (NSE) involving in a standard of content (SC), standard for educator and education staff (SEE), standard of facilities (SF), standard of assessment (SA), standard of the process (SP) and competence graduate standard (CGS) on achievement motivation (AM) and economics learning achievement (ELA), and to find out the indirect influence of SC, SEE, SF, SA, SP, and CGS on ELA through AM. This descriptive quantitative research used a survey to collect the data. The population is Indonesian senior high school students who have learned the economy for, at least. A total of 1065 students were selected through using proportional stratified random sampling with the Slovin formula (error=1%). The data in this study were collected through The data were subsequently analyized using Structural Equation Modeling (Partial Least Square approach). The result of this research showed that there was a direct effect of SC, SEE, SF, SA, SP, and CGS and AM on ELA. Then, there was an indirect effect of SC, SEE, SF, SA, and CGS on ELA through AM as a mediating variable.